2017
DOI: 10.5455/msm.2017.29.84-87
|View full text |Cite
|
Sign up to set email alerts
|

The Knowledge, Attitudes and Practices of Nurses Toward Management of Hospital-acquired Infections in the University Clinical Center of Kosovo

Abstract: Background:Hospital Acquired Infections (HAIs) are called those infections that were not present at the time of patient’ hospitalization in a hospital or other medical institutions and have been acquired after hospitalization.Aim:The aim of this paper was to investigate the level of knowledge, attitudes, and practices of nurses about preventing the spread and management of HAIs at University Clinical Center of Kosovo (UCCK).Methods:The questionnaire was used as a tool for data collection in 6 clinics of UCCK d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 23 publications
2
10
2
1
Order By: Relevance
“…This findings contradict the findings of a study 9 that indicated a quite a low level of safety knowledge among health care professionals. The findings of an another study 15 that investigated the level of knowledge, attitudes, and practices of nurses about preventing the spread and management of HAIs at University Clinical Center of Kosovo (UCCK) support the present study. The general level of knowledge of nurses about the spread of HAIs was 90%, about the attitudes was 84.4% and about the nurses' practices was 76.2%.…”
Section: Discussionsupporting
confidence: 82%
“…This findings contradict the findings of a study 9 that indicated a quite a low level of safety knowledge among health care professionals. The findings of an another study 15 that investigated the level of knowledge, attitudes, and practices of nurses about preventing the spread and management of HAIs at University Clinical Center of Kosovo (UCCK) support the present study. The general level of knowledge of nurses about the spread of HAIs was 90%, about the attitudes was 84.4% and about the nurses' practices was 76.2%.…”
Section: Discussionsupporting
confidence: 82%
“…A study published in Indonesia (2019) showed that training had a significant impact on the emergency nurses’ practice. 27 Another study published by Gruda and Sopjani’s, 28 in Kosovo (2017) showed that the work experience regarding the management of hospital-acquired infections had a significant relationship with the emergency nurses’ practices. Moreover, a study published in Saudi Arabia showed that over 5 years of ED experience had a more significant impact on emergency nurse and physician knowledge than practices and attitudes did.…”
Section: Discussionmentioning
confidence: 99%
“…Zahra Soleimani (Ph.D Student) 1,2 , Ali Mohammad Mosadeghrad (Ph.D) 3 , Masoumeh Abbasabadi (Ph.D) 4 , Marziyeh Moradi (Ph.D Student) 5 , Fatemeh Ashkani (B.Sc) 6 , Mohammad Reza Asgari (Ph.D) 7 , Alireza Mesdaghinia (Ph.D) *8…”
Section: Developing and Psychometric Testing Of A Questionnaire To Assess The Knowledge Attitude And Practice Of Paramedical Staffs Aboutmentioning
confidence: 99%